2010
DOI: 10.1007/s10212-010-0028-3
|View full text |Cite
|
Sign up to set email alerts
|

School’s out: a comprehensive follow-up study on parents’ perceptions of their child’s school

Abstract: This longitudinal study set out to examine the changes that took place in parents' evaluations of their child's school in the course of the child's complete 9-year-long compulsory education. Over the follow-up period, academically educated and vocationally educated mothers and fathers (N=326) were asked to indicate their degree of satisfaction with aspects of their child's school every 2 years. It was found that the level of parental satisfaction was fairly high at the start, that the general decreasing trend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
1
8
0
3
Order By: Relevance
“…The teachers confirmed that their relations with parents whose children hold office in the TCP were usually positive. All eight parents were highly involved in their children's educational follow‐up, as has also found in other Finnish studies on middle‐class parents and schooling (Metso, ; Räty, ; Räty and Kasanen, ). Board members confirmed their parents' interest in their schoolwork, for example, Kaisa reported that ‘mummy usually asks, almost every day, if I need help with my school work'.…”
Section: Middle‐class Families and The Tcpsupporting
confidence: 76%
See 3 more Smart Citations
“…The teachers confirmed that their relations with parents whose children hold office in the TCP were usually positive. All eight parents were highly involved in their children's educational follow‐up, as has also found in other Finnish studies on middle‐class parents and schooling (Metso, ; Räty, ; Räty and Kasanen, ). Board members confirmed their parents' interest in their schoolwork, for example, Kaisa reported that ‘mummy usually asks, almost every day, if I need help with my school work'.…”
Section: Middle‐class Families and The Tcpsupporting
confidence: 76%
“…By contrast, parents with lower education relate more to the idea of children's natural development and growth, which happens without too much interference from parents (e.g. Bæck, ; Räty, ; Räty and Kasanen, ). Moreover, numerous studies testify to how middle‐class parents promote their children's future careers via hobbies and extracurricular activities (e.g.…”
Section: Middle‐class Families Cultural Resources and Emotionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Se ha señalado que el nivel académico de los jefes de familia influye en el nivel de involucramiento en la vida académica de los adolescentes, es decir a mayor nivel de escolaridad toman mayor participación crítica que aquellos que demuestran menos niveles educativos (Räty, 2010). Ahora bien, según Toro, et.al.…”
Section: Antecedentes De La Literaturaunclassified